THE EFFECT OF CONCENTRATED OWNERSHIP ON BANK PROFITABILITY IN INDONESIA - Amanda, Michelle Priscilla; Lam, Serafina; ., Rinaningsih; Adelina, Yang Elvi (UI Scholars Hub, 2020)
This paper examines the association between concentrated ownership and the profitability of banks in Indonesia during the period from 2012 to 2018 with a total sample of 93 banks or 651 observations. This study applies the Random Effect regression method, and reveals a non-significant association between concentrated ownership and bank profitability as measured by ROA and ROE. It indicates that a majority of shareholders tend to use their power to exploit minority shareholders, which can also strengthen the monitoring effect. However, the regression also indicates that there is a significant non-linear relationship between concentrated ownership and profitability when measured by ROE. There is a mixed-effect between concentrated ownership and profitability in the case of Indonesian banks. Moreover, a regression is also utilized with dummy variables of concentrated ownership (FIN and IND) to assess the difference between non-financial institution ownership and financial institution ownership. The results show no significant difference in cases. This can be caused by institutional ownership (financial institutions), which only acts as a short-term trader that emphasizes short-term profits. Therefore, its existence as a shareholder is not any different to the presence of non-financial institution ownership. The findings of this study show that the application of POJK No. 56/POJK.03/2016 regarding Share Ownership of Commercial Banks which regulates the maximum limit of concentrated ownership in banks may not work effectively in strengthening bank performance.